1999
DOI: 10.1128/aac.43.2.335
|View full text |Cite
|
Sign up to set email alerts
|

Effects of NorA Inhibitors on In Vitro Antibacterial Activities and Postantibiotic Effects of Levofloxacin, Ciprofloxacin, and Norfloxacin in Genetically Related Strains of Staphylococcus aureus

Abstract: NorA is a membrane-associated multidrug efflux protein that can decrease susceptibility to fluoroquinolones in Staphylococcus aureus. To determine the effect of NorA inhibition on the pharmacodynamics of fluoroquinolones, we evaluated the activities of levofloxacin, ciprofloxacin, and norfloxacin with and without various NorA inhibitors against three genetically related strains of S. aureus (SA 1199, the wild-type; SA 1199B, a NorA hyperproducer with a grlA mutation; and SA 1199-3, a strain that inducibly hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
69
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(71 citation statements)
references
References 24 publications
(52 reference statements)
1
69
0
1
Order By: Relevance
“…NorA efflux activity in fluoroquinolone resistance was determined by MIC in the presence of reserpine, a NorA inhibitor. Minimal shifts in MIC for levofloxacin and up to 8-fold decrease in ciprofloxacin MIC indicate that NorA has minimal influence on fluoroquinolone resistance (Table S3) (Kaatz and Seo, 1995; Aeschlimann et al, 1999). mphC , a 2′-phosphotransferase which directly inactivates the macrolides via phosphorylation determines selective macrolide resistance (erythromycin) in UCH 121, UCH 127 and HH1184, all clonally distinct isolates(Matsuoka et al, 2003; Juda et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…NorA efflux activity in fluoroquinolone resistance was determined by MIC in the presence of reserpine, a NorA inhibitor. Minimal shifts in MIC for levofloxacin and up to 8-fold decrease in ciprofloxacin MIC indicate that NorA has minimal influence on fluoroquinolone resistance (Table S3) (Kaatz and Seo, 1995; Aeschlimann et al, 1999). mphC , a 2′-phosphotransferase which directly inactivates the macrolides via phosphorylation determines selective macrolide resistance (erythromycin) in UCH 121, UCH 127 and HH1184, all clonally distinct isolates(Matsuoka et al, 2003; Juda et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Norfloxacin (5), ciprofloxacin (9) and ofloxacin (11) seem to be affected more than sparfloxacin (13), gatifloxacin (15), sitafloxacin (18), gemifloxacin (19), moxifloxacin (20), trovafloxacin (21) and garenoxacin (22), suggesting that these last quinolones may be poorer substrates for these pumps [22,85,90,[92][93][94]. Thus, efflux-mediated resistance mechanisms seem to affect quinolone agents to different extents, depending on the physicochemical properties and structural characteristics of the individual quinolones.…”
Section: Resistance Among Gram-positives and Impact Of Quinolone Strumentioning
confidence: 90%
“…Previously, only hydrophilicity of the fluoroquinolones was thought to be an important factor for NorA-mediated transport. It was found that the NorA inhibitors reserpine and omeprazole dramatically improve the activities of the more hydrophilic quinolones [norfloxacin (5 ) and ciprofloxacin (9)] [93]. In addition, Hydrophilic quinolones, such as norfloxacin (5) and ciprofloxacin (9), appear more prone to efflux than more hydrophobic molecules like grepafloxacin (14) and gatifloxacin (15) in Gram-positive organisms such as S. pneumoniae [95,96].…”
Section: Resistance Among Gram-positives and Impact Of Quinolone Strumentioning
confidence: 98%
“…The pathways of adaptogenesis can be divided roughly into the following: a) Reduction of the ability of a compound to penetrate bacterial cells. This may be a consequence of the loss or a change of specific permeases, active blockage of access of compounds to the cell, and factors that actively eliminate xenobiotics from cells [1,2]; b) Change of metabolism that inactivates the compounds. This may be the loss of an exchange cycle that is sensitive to a given toxicant, increased synthesis of enzymes capable of modifying the poison, or the assimilation of specific products that reduce the toxicity of xenobiotics [3].…”
mentioning
confidence: 99%